Imagining Afghanistan : global fiction and film of the 9/11 wars (2019)
When photojournalist Lynsey Addario came back home to New York City in 2000, having traveled to Afghanistan still under the rule of the Taliban, she had trouble finding a venue for her photographs. She writes: “For a long time no newspaper or magazine bought them. In the year 2000 no one in New York was interested in Afghanistan” (77). At that time, Afghanistan was what object-oriented philosopher Levi R. Bryant would call a dim object—it emitted no light, attracted no attention, and the eyes of the world were not on it. This “dim” period lasted more or less from 1989—the year when the Soviet government made the decision to withdraw from Afghanistan (an event that marked the end of the Cold War, preceding the dissolution of the Soviet Union by two years)—to 2001, the year when the attacks on the World Trade Center in New York City shook the world. In the weeks following 9/11, as the United States was preparing to embark on Operation Enduring Freedom, the previously dim object suddenly became bright. As reporters rushed into Jalalabad, Kabul, Kandahar, and Herat, media outlets around the world were flooded with images of Afghanistan and its people.